Maternal factor and children’s nutrition status in senuro village, South Sumatera Province, Indonesia - Suci Destriatania; Rini Mutaha; Fatmalina Febry; Indah Purnama Sari (Universiti Kebangsaan Malaysia, 2011)
Approximately half a billion children under the age of five were living in developing countries. Out of these, about 37% are stunted, 11% are wasted and 30% are underweight1. Children malnutrition is one of serious health issues in Indonesia. The National Socio-Economic Survey noted that the prevalence of children with lack of nutrition increased from 2002 (18.3%) to 2003 (19.6%) and declined to18.8% in 20042. The prevalence of children with severe nutrition in South sumatera in 2003 is above of the national average of 8.5%2. According to the Basic Health Research in 2007, the prevalence of underweight and severely underweight in South Sumatera is high (11.7% and 6.5%, respectively)3. There is a strong association between malnutrition and child mortality, that a malnourished child tends to suffer more days of infectious disease. The simultaneous presence of malnutrition and infection greatly increased the child’s risk of death. Most of the children in the developing world die, not from starvation or infectious disease alone, but from the simultaneous presence of malnutrition and infection together4. The causes of malnutrition are numerous. The proximate determinants of malnutrion are poor diet and illness. Poor diet and illness are themselves caused by underlying factors which include maternal child taking practices. The aims of this study are to asses nutritional status and determine maternal potential risk factors including breastfeeding and weaning practices of mother, mother’s education, occupation and nutritional knowledge to malnutrition in children under age five in Senuro Village, South Sumatera Province.